Tumor microenvironment activated chemodynamic–photodynamic therapy by multistage self-assembly engineered protein nanomedicine - Zhang, Qiuhong (2022)
While cytotoxic reactive oxygen species (ROS) play an important role in fighting cancer, developing an activable ROS-generating system to achieve highly specific cancer therapy with minimum side effects to normal tissues remains challenging. This work reports the development of a tumor microenvironment-activable ROS-generating system via multistage self-assembly engineered protein-based nanomedicine containing cascade enzymes and photosensitizers. The multistage self-assembly-induced aggregation not only prevents the premature exposure of cascade enzymes to produce toxic by-products in noncancerous sites, but also quenches the photosensitizers to diminish skin phototoxicity, contributing to effective self-protection of normal tissues. Once triggered by the intratumoral reduction microenvironment, the aggregation effect is unlocked to expose cascade enzymes and recover the photosensitivity, which can decompose intratumor glucose for hydroxyl radical generation and respond to external laser irradiation for singlet oxygen production respectively, realizing tumor-specific chemodynamic–photodynamic combinational therapy. This work demonstrates a protein-based multistage self-assembly approach for ROS-mediated cancer-specific therapy with effective self-protection, offering a powerful strategy for nanomedicine design and more precise cancer therapy.